2013
DOI: 10.12816/0000081
|View full text |Cite
|
Sign up to set email alerts
|

Tooth and Gingival Display in the Anterior Region at Rest and during Smiling of Different Age Groups : A Comparative Study

Abstract: Objective: To investigate the effect of age on the degree of maxillary and mandibular anterior teeth and associated gingival display when the lips are at rest and during smiling among a group of Jordanian population. Methods: A total of 127 subjects (74 females and 53 males) were included in this study. Subjects had all natural anterior teeth present with no caries, restorations, extreme occlusal wear, extrusion, obvious deformities, or tooth mobility. Crown length, displayed portions of maxillary and mandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…The difference of LL at rest and on smiling was however found to be more in females than the males indicating a fuller smile exhibited by the females. These findings of difference in LL are similar to the ones reported by Al‐Habahbeh et al 7 where the authors reported a lip elevation of 5.2 mm and 23% decrease in LL, though the segregation based on gender was not reported. In another study by Miron H et al 9 the maxillary lip at rest was found to be 3 mm shorter in females than the males and the authors attributed the differences to the simple biologic scaling clearly indicating sexual dimorphism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The difference of LL at rest and on smiling was however found to be more in females than the males indicating a fuller smile exhibited by the females. These findings of difference in LL are similar to the ones reported by Al‐Habahbeh et al 7 where the authors reported a lip elevation of 5.2 mm and 23% decrease in LL, though the segregation based on gender was not reported. In another study by Miron H et al 9 the maxillary lip at rest was found to be 3 mm shorter in females than the males and the authors attributed the differences to the simple biologic scaling clearly indicating sexual dimorphism.…”
Section: Discussionsupporting
confidence: 90%
“…The amount of tooth visibility is definitively determined by the muscle position at rest whereas during smiling it is ascertained by dynamic muscular position of the lips 4,5 . So essentially, the degree of tooth display in the maxillary anterior region at rest position and while smiling is dependent on positions of the maxillary and mandibular lips 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Correia et al [ 12 ] evaluated the intercommissural distance, proposing that changes in this variable could explain the exposure of lower teeth in elders, suggesting that changes in the muscle tone might interfere with this distance. Al-Habahbeh et al [ 40 ] and Dindaroğlu et al [ 20 ] reported an inversion in the exposition of teeth, with a decrease for the upper teeth and an increase in the lower teeth exposition with aging. This event can be caused by the loss of lip elasticity, lower migration of the surrounding soft tissues, and the wear of the anterior teeth causing their shortening [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some cross-sectional studies have suggested that the mean value of incisal show at rest should be 2 to 3 mm and could be differentiated between male and female individuals, different races, and different lip shapes. [59][60][61] Therefore, our average three-dimensional skeletofacial models require some modifications to approximate the size of the frontal and orbital areas, which entails rotating the template to mimic a patient's skeletal pattern. Moreover, clinical evaluation is still required after simulations using the average threedimensional skeletofacial models.…”
Section: Clinical Applicationmentioning
confidence: 99%